Online community information : creating a nexus at your library - Durrance, Joan C. (American Library Association, 2002)
"Presents the highlights of a 1998-2000 IMLS National Leadership Grant, 'Help-seeking in an electronic world: the role of the public library in helping citizens obtain community information over the Internet'"--Page ii